Analysis of research hotspots in oil & gas storage and transportation based on reports in Engineering Fronts and databases for retrieval - Zhaoyang LIU; Zhongyuan GUAN; Jiaxiong ZHAO; Peilu WU; Teng ZHANG; Mengyao QI (You-qi chuyun)
Objective As energy transition progresses, oil & gas resources will remain vital as energy and chemical raw materials, significantly contributing to global economic recovery, the development of the new energy system, and the improvements of production and living standards. With the expansion of the oil & gas pipeline network, the scope of objects transported by pipelines has also been broadened to include new energies such as hydrogen, methanol and ammonia, as well as unconventional media such as CO2, thereby introducing numerous new research topics in the field of oil & gas storage and transportation engineering. Methods Taking the reports of Engineering Fronts, the platforms of CNKI and SciVal, and core collections of Web of Science (WoS) as data sources, contents reflecting the development trends of science and technology in the industry were analyzed, such as the international cutting-edge research hotspots in oil & gas storage and transportation engineering field, as well as the high-frequency key words and the number of articles related to the hotspots in CNKI database, Scopus database and WoS core collections. The analysis thoroughly examined current scientific research hotspots and potential future development directions in this field. Results The analysis of topics in Engineering Fronts identified two key development directions: "deep ocean water" oil & gas resource development, storage and transportation, as well as oil & gas storage and transportation engineering empowered by artificial intelligence (AI). Utilizing data from the CNKI platform, recent articles published in Oil & Gas Storage and Transportation were analyzed, revealing the following development trends: hydrogen energy storage and transportation, inline inspection of pipelines, CO2 storage and transportation, and multi-energy integrated and flexible transportation of oil & gas pipeline networks. The cloud chart analysis of SciVal topic groups revealed the following development directions: pipeline safety, risk assessment, carbon emission control and environmental impact assessment, and oil & gas leakage and emergency response. Additionally, the analysis of research hotspots in the oil & gas storage and transportation engineering field, based on WoS core collections, identified development directions including pipeline fluid behavior, pipeline design, damage prevention, system optimization, risk management, material performance, intelligent control, and pipeline feature extraction and data analysis. Analysis of contributor countries and organizations in this field, based on WoS core collections, revealed that China, the United States, Germany, and the United Kingdom produced the most articles in the past five years, with China accounting for 31.46% of the total. The top contributing organizations were the Chinese Academy of Sciences, China University of Petroleum, and the United States Department of Energy. Ongoing attention to the research and development trends from these countries and organizations was recommended. Conclusion The future development directions of oil & gas storage and transportation engineering primarily include: (1) full integration of AI with storage and transportation technologies; multienergy integrated transportation and Energy Internet development in line with the dual carbon strategy; (2) advancements in submarine pipeline planning, design, laying, risk monitoring, and emergency response to support the utilization of deep-sea oil & gas resources; (3) the establishment of "one pipeline network nationwide" for both sea and land pipelines; and (4) continuous improvement of the environmental protection and ecological safety in the planning and construction of oil & gas pipeline engineering through both conceptual and technical advancements.